Testing of Saline–Alkali Tolerance in Oat Germplasm Through Integrated Germination and Field Performance Assessments - Biru Zhang; Junzhen Mi; Baoping Zhao; Zhongshan Xu; Xingyan Li; Jinghui Liu; Zhiqiang Yuan (Agronomy)
Oats are an important grain-feeding crop with strong saline–alkali tolerance; however, the genetic mechanism of this tolerance is not clear, which hinders the development of oat varieties adapted to saline soils. In this study, the saline–alkali tolerance of 524 oat germplasm resources was comprehensively evaluated using culture-dish germination and field identification methods. During the germination period, saline–alkali stress significantly inhibited the germination potential, germination rate, and shoot and root lengths of oat germplasm. The indicators decreased by 71.15%, 49.32%, 59.03%, and 63.90%, respectively. The relative value of each trait was used as the evaluation metric. The 524 oat germplasm resources were classified into five groups by cluster analysis, and 174 oat germplasm resources with saline-alkali tolerance at the germination stage were screened. A regression equation for the identification of germinated saline-alkali-tolerant oat germplasm resources under the same conditions was also established. The field experiment showed that the coefficients of variation of oat germplasm resources were 4.03–54.12% and 6.97–38.50% in the two locations, which was rich in genetic variation; the correlation analysis showed that the biological yield was positively correlated with the D-value, and 18 high–quality and high-yielding saline–alkali-tolerant oat germplasm resources were identified by combining the saline–alkali-tolerant and weak germplasm resources of the two locations. Based on the multidimensional evaluation of germination and field performance, the 18 saline–alkali–tolerant germplasms screened in this study provide high–quality germplasm resources and a theoretical basis for saline oat cultivation and saline-tolerant breeding.